Consistent multi-layer subtask tracker via hyper-graph regularization. (July 2017) - Fan, Baojie; Cong, Yang
Highlights: Develop the online multi-subtask learning framework for robust object tracking with novel task definition. The relationships among and inside candidates or training samples are mined by hyper-graph regularization. Simultaneously learn and update the adaptively discriminative subspace and classifier. Consistent multi-subtask tracker is a general model for most existing multi-task trackers. Abstract: Most multi-task learning based trackers adopt similar task definition by assuming that all tasks share a common feature set, which can't cover the real situation well. In this paper, we define the subtasks from the novel perspective, and develop a structured and consistent multi-layer multi-subtask tracker with graph regularization. The tracking task is completed by the collaboration of multi-layer subtasks. Different subtasks correspond to the tracking of different parts in the target area. The correspondences of the subtasks among the adjacent frames are consistent and smooth. The proposed model introduces hyper-graph regularizer to preserve the global and local intrinsic geometrical structures among and inside target candidates or trained samples, and decomposes the representative matrix of the subtasks into two components: low-rank property captures the subtask relationship, group-sparse property identifies the outlier subtasks. Moreover, a collaborate metric scheme is developed to find the best candidate, by concerning both discrimination reliability and representation accuracy. We show that the proposed multi-layer multi-subtask learning based tracker is a general model, which accommodates most existing multi-task trackers with the respective merits. Encouraging experimental results on a large set of public video sequences justify the effectiveness and robustness of the proposed tracker, and achieve comparable performance against many state-of-the-art methods.